Operational Noise Assessment in an Open Cycle Power Plant: Study on the Existing Acoustical Performance. - Halim, Helmi A; Hayder, Gasim (International Journal of Engineering and Technology, 2018)
This research is an acoustical performance study in an open cycle peaking gas turbine power plant located at the southern coast of Peninsula Malaysia. Referring to its location at the middle of residence and tourism area, throughout its operation years, several complains from public has been lodged about the excessive operational noise at the perimeter of the plant and statistically from the last decade, twenty-four (24) noise related public complains were recorded. This issue has initiated a study to determine the current operational noise level as well as the effectiveness of the existing noise barriers. Based on EIA approval, the boundary noise for the operation should be limited to 55 dB(A) at any time. The field measurement of noise level at two (2) different locations are assessed in-situ and continuously noise monitoring covering all the plant’s operational regime and at different plant operational pattern. These results are compared with the initial noise report during its early year of operation in 1999. Finally the hypotheses then compared with the referenced legislations. Results from all the methodologies show the current operational noise level of the plant are within the permissible limit, however the overall operational noise of the plant is increasing compared with 1999 report due to the increasing of surrounding activities as well as deteriorating of current engineering and natural noise barrier arrangement. Mitigation plans has been recommended to the management to minimize the impact of the excessive noise to surrounding residence and to the plant workers. On top of that, the theoretical and commercial implication of the research is also discussed.